Nurses and the disabled child’s perspective in the anaesthesia procedure preparation process using a picture schedule - Johanna Kaitsalmi; Tanja Vehkakoski; Liisa Karlsson; Sanna Salanterä (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study’s purpose was to investigate how nurses, using a picture schedule, enable or hinder the realization of disabled children’s agency in the preparation for an MRI procedure carried out under general anaesthesia. Methods A qualitative observation study was used to explore the interaction of nurses and children. The data consisted of video recordings of 25 preparation situations of 3 (3–8 years old) children (with challenges in communication and/or cognitive skills) with 4 nurses. Verbal and nonverbal communication was analysed with interventionist applied conversation analysis. Results What was most crucial was how the picture schedule was used during the interaction. Reciprocal information sharing, responding to the child’s initiatives by negotiating and allowing the child to take physical action with the picture schedule enabled the realization of the child’s agency. Conclusions The preparation process should aim to help the child prepare in his/her own way. The preparation tools should encourage reciprocal interaction in informing and in responding to the children’s initiatives. The preparation practices should include enough time for the child’s initiatives and physical participation. The results can be used in assessing preparation tools and how they are used from the perspective of the child’s agency.